Reflective Coaching for the Development of Pedagogical Content Knowledge of Biology Teachers in Thailand - Thiliworrakan, Nunnapat; Ladachart, Ladapa (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
This research aims to determine the effects of reflective coaching on developing pedagogical content knowledge (PCK) of biology teachers regarding cell biology. The research used qualitative research conducted with four participants to gain deeper insights into the topic rather than the broad consensus. The instruments used in the research consisted of teaching observation records, reflective coaching record forms, and Pedagogical Content Knowledge (PCK) tests. In addition, PCK questionnaires and interviews were subjected to content analysis with analytic induction were used to for data triangulation. The research results have commonly patterned that the level of PCK changed after reflective coaching but did not change every element of PCK. The participants still had limited knowledge of teaching methods in cell biology content. Differences were observed in each element of PCK, including information helping to support that science teacher professional development that should focus on promoting PCK. In summary, the participants could develop PCK in cell biology content with different reflection algorithms and methods as the experience and prior knowledge of individual case studies are different. The need for self-development in each element of PCK also differs. This may require various methods, such as self-reflection of the problem, self-assessment, and learning notes. Knowledge from this study can be applied in solving problems of individual teachers and benefit the teaching profession’s development .